A POETIC Phase II study of continuous oral everolimus in recurrent, radiographically progressive pediatric low‐grade glioma. Issue 2 (2nd November 2020) - Wright, Karen D.; Yao, Xiaopan; London, Wendy B.; Kao, Pei‐Chi; Gore, Lia; Hunger, Stephen; Geyer, Russ; Cohen, Kenneth J.; Allen, Jeffrey C.; Katzenstein, Howard M.; Smith, Amy; Boklan, Jessica; et al.
Abstract: Background: To evaluate efficacy, pharmacokinetics (PK) and pharmacodynamics of single‐agent everolimus in pediatric patients with radiographically progressive low‐grade glioma (LGG). Methods: Everolimus was administered at 5 mg/m 2 once daily as a tablet or liquid for a planned 48‐week duration or until unacceptable toxicity or disease progression. Patients with neurofibromatosis type 1 were excluded. PK and pharmacodynamic endpoints were assessed in consenting patients. Results: Twenty‐three eligible patients (median age 9.2 years) were enrolled. All patients received prior chemotherapy (median number of prior regimens two) and/or radiotherapy (two patients). By week 48, two patients had a partial response, 10 stable disease, and 11 clinical or radiographic progression; two discontinued study prior to 1 year (toxicity: 1, physician determination: 1). With a median follow up of 1.8 years (range 0.2‐6.7 years), the 2‐, 3‐, and 5‐year progression‐free survivals (PFS) were 39 ± 11%, 26 ± 11%, and 26 ± 11%, respectively; two patients died of disease. The 2‐, 3‐, and 5‐year overall survival (OS) were all 93 ± 6%. Grade 1 and 2 toxicities predominated; two definitively related grade 3 toxicities (mucositis and neutropenia) occurred. Grade 4 elevation of liver enzymes was possibly related in one patient. Predose blood levels showed substantial variability between patients with 45.5% below and 18.2% above the target range of 5‐15 ng/mL. Pharmacodynamic analysis demonstrated significant inhibition in phospho‐S6, 4E‐BP1, and modulation of c‐Myc expression. Conclusion: Daily oral everolimus provides a well‐tolerated, alternative treatment for multiple recurrent, radiographically progressive pediatric LGG. Based on these results, everolimus is being investigated further for this patient population.